Proteomic analysis of bioactive peptide from different plant parts of Phyllanthus Niruri (Dukung Anak) and its anti-diabetic propertes - Mohd Nail, Ainul Mardhiah; Md Zin, Noor Hasniza; , (2015)
Herb Phyllanthus niruri (P. niruri) is known to have various pharmacological functions including anticancer, antibacterial, antioxidant, anti-hypertensive and also anti-diabetic properties. In this research, the proteomic part of P. niruri was studied to determine the bioactive peptides that responsible for specific characteristics. Total soluble proteins from different plant parts of freshly collected P. niruri were extracted using TCA/acetone method and then quantified using Bradford assay. Fruits part was found to have a significantly higher amount of proteins (4.91µg/µl + 0.21) compared to leaves (4.18µg/µl + 0.15). To determine the quality of proteins in the crude extract, SDS-Page was carried out which separates proteins in the basis of molecular weight. Proteins extracted from leaves were widely distributed between the range of 3.5 kDa to 160 kDA. Meanwhile, proteins in fruits mainly distributed within the range of 15 kDa to 80 kDa. The most highly expressed protein band was found in fruit, located in between 30 to 40 kDa. The protein extracts were then further analyzed based on the molecular weight and isoelectric points using two-dimensional gel electrophoresis (2D-GE) approach. Based on the profile pattern obtained from 2D-GE analysis, protein extract from fruits seems to express more protein spots compared to protein extract from leaves. Protein spots from fruit are seen to be intensely resolved within pH 4 to 10 at molecular weight between 10 kDa to 80 kDa. On the other hand, protein spots from leaves were moderately resolved at pH 4 to 10 at molecular weight within 10 kDa to 50 kDa.